Application of three‑dimensional printing for colon targeted drug delivery systems - Charbe, Nitin B; McCarron, Paul A; Lane, Majella E; Tambuwala, Murtaza M (International Journal of Pharmaceutical Investigation)
Orally administered solid dosage forms currently dominate over all other dosage forms and routes of administrations. However, human gastrointestinal tract (GIT) poses a number of obstacles to delivery of the drugs to the site of interest and absorption in the GIT. Pharmaceutical scientists worldwide have been interested in colon drug delivery for several decades, not only for the delivery of the drugs for the treatment of colonic diseases such as ulcerative colitis and colon cancer but also for delivery of therapeutic proteins and peptides for systemic absorption. Despite extensive research in the area of colon targeted drug delivery, we have not been able to come up with an effective way of delivering drugs to the colon. The current tablets designed for colon drug release depend on either pH‑dependent or time‑delayed release formulations. During ulcerative colitis the gastric transit time and colon pH-levels is constantly changing depending on whether the patient is having a relapse or under remission. Hence, the current drug delivery system to the colon is based on one‑size‑fits‑all. Fails to effectively deliver the drugs locally to the colon for colonic diseases and delivery of therapeutic proteins and peptides for systemic absorption from the colon. Hence, to overcome the current issues associated with colon drug delivery, we need to provide the patients with personalized tablets which are specifically designed to match the individual’s gastric transit time depending on the disease state. Three‑dimensional (3D) printing (3DP) technology is getting cheaper by the day and bespoke manufacturing of 3D‑printed tablets could provide the solutions in the form of personalized colon drug delivery system. This review provides a bird’s eye view of applications and current advances in pharmaceutical 3DP with emphasis on the development of colon targeted drug delivery systems.
Keywords: Colitis; colon drug delivery; personalized medicine; three‑dimensional printing